A Catalytic Microwave Process for Superfast Preparation of High‐Quality Reduced Graphene Oxide. (4th October 2017) - Liu, Runze; Zhang, Yu; Ning, Zhenjian; Xu, Yuxi
Abstract: Herein we report that a small amount of graphite can unexpectedly act as the catalyst to greatly promote the microwave exfoliation and reduction of graphite oxide in ambient air. The reaction can be finished in a few seconds in contrast to more than ten minutes without catalyst. The catalytic microwave exfoliated graphite oxide (CMEGO) is of higher quality than the traditional microwave exfoliated graphite oxide, including a much higher exfoliation degree with thinner graphene sheets and higher specific surface area (886 m 2 g −1 vs. 466 m 2 g −1 ), a much larger C/O ratio (19.4 vs. 6.3) and a higher lattice crystallinity, as well as significantly improved electrical conductivity (53180 S m −1 vs. 5140 S m −1 ). The CMEGO is used as anode for lithium‐ion battery (LIB) and sodium‐ion battery (SIB), and delivers ultrahigh reversible capacities, remarkable rate capabilities, and superior cycling stabilities in both LIB and SIB.